2019
DOI: 10.1038/s41416-019-0476-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and quality assessment of individualised breast cancer risk prediction models

Abstract: BackgroundIndividualised breast cancer risk prediction models may be key for planning risk-based screening approaches. Our aim was to conduct a systematic review and quality assessment of these models addressed to women in the general population.MethodsWe followed the Cochrane Collaboration methods searching in Medline, EMBASE and The Cochrane Library databases up to February 2018. We included studies reporting a model to estimate the individualised risk of breast cancer in women in the general population. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 43 publications
4
88
0
Order By: Relevance
“…Our results suggest that VASS has a stronger dependence on breast cancer risk than MPD and therefore has the potential to increase precision in standard risk models. Current methods of measuring BD based on mammography, either by radiologist's estimation or computer-assisted measurement, limit the risk stratification achievable by the inclusion of BD in risk models [2]. Potential reasons for the stronger observed effects for VASS versus MPD include the true volumetric nature of BD assessment by UST of the uncompressed breast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that VASS has a stronger dependence on breast cancer risk than MPD and therefore has the potential to increase precision in standard risk models. Current methods of measuring BD based on mammography, either by radiologist's estimation or computer-assisted measurement, limit the risk stratification achievable by the inclusion of BD in risk models [2]. Potential reasons for the stronger observed effects for VASS versus MPD include the true volumetric nature of BD assessment by UST of the uncompressed breast.…”
Section: Discussionmentioning
confidence: 99%
“…Mammographic percent density (MPD) is a strong breast cancer risk factor that typically confers a three-to fivefold elevation in risk for the highest versus lowest levels of density [1]. Given that breast cancer risk prediction models under-perform with regard to estimating individual risk, researchers have attempted to incorporate MPD into such models to improve their performance (as recently reviewed in Louro et al [2]). Multiple studies [2] have found that adding MPD to risk models improves breast cancer risk prediction, and efforts to incorporate MPD in newer risk models are ongoing [3,4]; however, to date, improvements in discriminatory accuracy have been modest.…”
Section: Introductionmentioning
confidence: 99%
“…This may require worldwide multicenter collaborations to reach solid conclusions. For example, prognostic risk calculators have been in use for risk predication in other malignancies [69,70]. Although we have some prognostic calculators for ACC [36,46,47], none have been prospectively validated, which limits their use in decision-making.…”
Section: Future Directionsmentioning
confidence: 99%
“…Risk estimation in this setting rests on the use of statistical models; many are available and can be accessed with ease online 30‐34 . Selection of an appropriate risk model is somewhat dependent upon the population served and the reason for clinical implementation, and none is clearly superior 35,36 . The earliest validated risk assessment model was developed by Gail et.al., 37 and over the years, it has been re‐evaluated many times and has shown good calibration with marginal discrimination, particularly for ER‐negative breast cancer 38 .…”
Section: Components Of a Comprehensive Breast Cancer Risk Assessment mentioning
confidence: 99%